Understanding Echinococcosis: A review of its epidemiological outlook (Bangladesh Journal of Zoology, 2025)
Echinococcosis is an ignored silent cyclozoonotic illness in many resource-poor pastoral regions impacting a variety of animal species, such as  wildlife and cattle, causes of substantial morbidity and mortality and it also has zoonotic implications. The damage produced by these tapeworm larvae constitutes a complicated and multi-faceted threat to human health. This manuscript digs into the essence of this parasite ailment, examining its causative agents, varied forms, and perilous dissemination. The diagnosis becomes a detective story, employing immunological clues and imaging's vigilant eye. Finally, the vital role of prevention, a harmonious concerto including deworming, hygiene, and education, takes the stage, trying to silence the parasite's silent melody. This abstract is a call to action, a rallying cry against the silent pain produced by echinococcosis. Echinococcosis, with its many forms and convoluted life cycle, reminds us of the intricate interactions between people, animals, and the environment in the world of infectious diseases. By understanding its complexities, we may work towards effective prevention, diagnosis, and treatment, guaranteeing a safer travel for all.Bangladesh J. Zool. 53(1): 03-18, 2025